EXPLORING METHODS FOR ASSESSING ELECTRICAL CONDUCTIVITY IN MATERIALS AND BODIES - G.M. Mo’minova (Лучшие интеллектуальные исследования, 2024)
Abstract: Understanding the electrical conductivity of various materials and bodies is crucial for numerous industrial, scientific, and technological applications. This article reviews and compares various methods utilized to measure electrical conductivity, ranging from conventional techniques to advanced methodologies. The discussion encompasses principles, instrumentation, advantages, and limitations of each method, providing valuable insights for researchers, engineers, and practitioners in diverse fields.